Can Impaired Elasticity of Aorta Predict the Success of Vardenafil Treatment in Patients with Erectile Dysfunction? - Hüseyin Ede; Serhat Tanik; Barış Yaylak; Kürşad Zengın; Sebahattin Albayrak; Suleyman Akkaya; Cegergun Polat; Yaşar Turan; Alirıza Erbay (Scientifica)
Objective. Vardenafil is used in treatment of erectile dysfunction (ED) but reveals variable clinical outcomes. Here, we aimed to evaluate the role of aortic elasticity in predicting vardenafil success among patients with ED. Methods. Sixty-one consecutive male subjects with primary ED and indication for vardenafil treatment were included. All subjects fulfilled 5-item version of the International Index of Erectile Function (IIEF-5) before the vardenafil treatment. Pretreatment aortic stiffness index (ASI) and aortic distensibility (AD) were obtained echocardiographically. Following two-month vardenafil treatment, the patients were reevaluated with IIEF-5. Pretreatment, posttreatment, and ΔIIEF-5 scores and ASI values were compared. Results. Average age was 54±8 years. Pretreatment and posttreatment IIEF-5 and ΔIIEF-5 scores were 9.1±2.5; 18.5±2.3; and 9.4±3, respectively. Mean ASI and AD values were 3.10±0.54 and 4.13±2.55 1/(103  ×  mmHg) accordingly. ASI value of severe pretreatment ED (n=15) was significantly higher than that of mild-moderate pretreatment ED (n=12) (p<0.001). All pretreatment IIEF-5 scores increased significantly compared to posttreatment IIEF-5 scores (p<0.001). ASI values were significantly correlated to pretreatment IIEF-5 scores (p<0.001) and ΔIIEF-5 value (p<0.001) but not to posttreatment IIEF-5 score. Conclusion. Aortic elasticity was impaired in accordance with degree of ED. The subjects with higher ASI values obtained more benefits from vardenafil.